Productive, Reproductive and Community Roles of Women Who Process Green Shells in Muara Angke, North Jakarta - Yekti Wahyuni (Yayasan Jurnal Perempuan, 2017)
This study aims to find out the productive, reproductive and community roles of fisherwomen in Muara Angke, Kecamatan Penjaringan, North Jakarta. The subjects of the study were two fisherwomen who work in the processing of green shells, as owners and as shellpeelerlaborer. The study explores women’s experience as breadwinners in the marine sector including the experience as a catch fisherwomen. The results showed that the role of fisherwomen in the productive and improvement of the family economy is very real,either directly or indirectly as a fisherwomen or processor of marine products. Three roles of fisherwomen in Muara Angke, sub-district Penjaringan, North Jakarta namely productive, reproductive, and social community. The fisherwomen took part in supplementingfamily income. In addition to performing reproductive roles related to domestic work, fisherwomen also have an active social role in social movements in order to maintain their living spaces and their spheres. The study found the tendency of women to abandon therole of capture fisherwomen when carrying out the role of biological reproduction.